Investigation of bending angle algorithm and path planning for puncture needles in transjugular intrahepatic portosystemic shunt - Qinmei Liao; Bing Li; Xihao Hu; Xiaoyun Huang; Jiacheng Guo; Yuanzhong Zhu; Wenjing He (BioMedical Engineering OnLine)
Abstract Purpose Design an algorithm to calculate the bending angle of the puncture needle for transjugular intrahepatic portosystemic shunt (TIPS) procedures and achieve three-dimensional visualized path planning. Materials and methods Based on enhanced CT images, a thresholding segmentation method was used to perform three-dimensional reconstruction of the hepatic vasculature, with the target puncture point selected by the interventional physician. The puncture needle was modeled using second-order Bézier curves and arcs. Subsequently, the bending points were selected, and the optimal bending angles were calculated based on the target puncture point. The puncture pathway was then verified and visualized in three dimensions using Mimics software. Data from 32 patients who successfully underwent TIPS procedures were retrospectively collected for clinical validation and statistical analysis. Results The error between the tip position of the puncture needle catheter modeled with Bézier curves and the actual puncture needle was 0.15 cm, while the error for the arc modeling was 0.19 cm. The optimal bending angle of the puncture needle calculated by this algorithm was validated in Mimics software, successfully achieving path planning. Among the 32 patients, the difference between the actual bending angle of the puncture needle and the calculated bending angle was 1.06° ± 1.82° (95% CI 0.41–1.72°). The equivalence test results indicated that there was a significant equivalence between the measured angle and the angle calculated by the algorithm (p < 0.001). Conclusion This study successfully designed an algorithm for calculating the bending angle of the puncture needle in TIPS procedures, which demonstrated equivalence with the clinically observed bending angles.